Mimicking the Human Body: The Rise of Organ-on-a-Chip Technologies - Sonawani, Radhika A.; Dhavane, Shweta S. (Asian Journal of Pharmaceutical Research and Development, 2025)
Organ-on-a-Chip (OoC) technology is transforming the way scientists study human biology by recreating organ functions on microfluidic chips. These small-scale devices replicate the conditions of human tissues, providing more accurate models for drug testing, disease research, and biological studies. Unlike traditional methods such as animal testing or 2D cell cultures, OoCs offer a more precise understanding of how organs work and respond to treatments. Advances in tissue engineering and microfabrication have led to the development of increasingly complex OoC systems. These platforms now allow for the study of multiple organ interactions, as well as the use of patient-specific cells to explore personalized treatments. Applications range from understanding diseases to testing drug safety and efficacy, with significant potential to reduce the high failure rates seen in clinical trials. As OoC technology continues to advance, its role in medical research and personalized medicine is expected to expand, offering a promising alternative to conventional testing methods and helping to pave the way for more effective therapies. The review highlights how OoCs have progressed from basic models to more complex systems, incorporating multiple cell types and even linking different organs together on a single chip. These advancements offer new insights into how the body works and how diseases develop, helping to speed up drug discovery and improve the testing of new treatments. OoC technology is also opening doors to personalized medicine by enabling experiments with cells derived from individual patients. Looking ahead, OoCs are set to become even more sophisticated, with the potential to model entire systems of the body. This could lead to more effective therapies and a better understanding of human biology, while reducing reliance on less accurate testing methods.